2011
DOI: 10.1097/aln.0b013e318206ff6f
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Orexin-A Is Mediated by an Increase of Hypoxia-inducible Factor-1 Activity in Rat

Abstract: Background: Recent studies suggest that the novel neuropeptide orexin-A may play an essential role during neuronal damage. However, the function of orexin-A during brain ischemia remains unclear. Recently, hypoxia-inducible factor-1␣ (HIF-1␣) was shown to be activated by orexin-A. The aim of the current study is to test the hypothesis that administration of exogenous orexin-A can attenuate ischemia-reperfusion injury through the facilitation of HIF-1␣ expression. Methods: Sprague-Dawley rats were subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 49 publications
4
58
0
1
Order By: Relevance
“…In addition, the level of orexin-A in cerebrospinal fluid was found to be reduced in subsets of patients with vascular diseases (Ripley et al, 2001). The mechanisms of the neuroprotective effects of orexin-A have been proven to be related with some intracellular signal transduction pathway, such as hypoxia-inducible factor-1a (Yuan et al, 2011). Therefore, it was hypothesized that hypothalamic orexin-A might be involved in the development of postischemic glucose intolerance and neuronal damage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the level of orexin-A in cerebrospinal fluid was found to be reduced in subsets of patients with vascular diseases (Ripley et al, 2001). The mechanisms of the neuroprotective effects of orexin-A have been proven to be related with some intracellular signal transduction pathway, such as hypoxia-inducible factor-1a (Yuan et al, 2011). Therefore, it was hypothesized that hypothalamic orexin-A might be involved in the development of postischemic glucose intolerance and neuronal damage.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Examining the relationship between traditional risk factors for cardiovascular disease and stroke might clarify the associations between CSF orexin-A concentrations and cerebrovascular infarction. Yuan et al 20 showed that orexin-A treatment can induce prominent neuroprotective effects on transient cerebral ischaemia in rats by improving neurological function and decreasing infarct size. In the authors' opinion, serum orexin-A is not a useful indicator for the prediction of symptomatic brain ischaemic infarction, but lower orexin-A concentrations in the CSF may be related to ischaemic injury.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mTORC1 positively regulates the activities of SREBP1 and PPAR␥, the two transcription factors that control expression of proteins involved in lipid and cholesterol homeostasis (65,66). Moreover, mTORC1 activates the transcription factor HIF1␣ to stimulate specific metabolic pathways, including glycolysis and the oxidative arm of the pentose phosphate pathway (65,(67)(68)(69). Therefore, the orexin-mTORC1 signaling axis may provide a plausible explanation for the metabolic phenotypes resulting from chronic gain or loss-of-function of orexin/GPCR signaling.…”
Section: Does the Mtorc1 Pathway Contribute To Functions Of Orexin Inmentioning
confidence: 99%